Integrating multimodal scaffolding in business english reading using the superstar platform: a systematic literature review - Peng xiaohua; Wirawati Ngui Yi Xe; Asmaa AlSaqqaf (Penerbit Universiti Malaysia Sabah, 2024)
Business English (BE) classes in college require reading proficiency. Multimodal scaffolding (MS), which uses many media to adapt instruction, is growing in popularity. This review evaluates MS on the Superstar Platform for college-level BE reading. The paper begins with a theoretical framework that explains scaffolding in language acquisition and the importance of MS in instructional design. Scaffolding in language acquisition, MS's impact on reading comprehension, and digital learning environments in language training are examined in the article. The research procedure and study selection criteria are described. The paper studies Superstar as a framework and finds MS methods that match the platform's properties. It also examines successful case studies using these tactics. The results show that MS via Superstar increases college BE students' language and problem-solving skills. The essay emphasizes MS's self-regulation, engagement, and autonomous learning benefits over conventional techniques. The study offers instructors pedagogical tips for using MS efficiently to meet the requirements and ability levels of a variety of students. The report suggests future research based on the newest BER course learning and technology integration breakthroughs, notwithstanding its implementation challenges.